A simple algorithm for optimal design in distributed fibre-optic sensing. Issue 1 (23rd November 2022) - Fichtner, Andreas; Hofstede, Coen
SUMMARY: We present a basic algorithm for optimal experimental design in distributed fibre-optic sensing. It is based on the fast random generation of fibre-optic cable layouts that can be tested for their cost-benefit ratio. The algorithm accounts for the maximum available cable length, lets the cable pass through pre-defined points of interest, avoids obstacles that the cable must not traverse, permits the adaptation of geometric complexity of different cable segments and allows for the incorporation of topography. Furthermore, the algorithm can be combined with arbitrary measures of the cost-benefit ratio, and its simplicity enables easy adaptations to the needs of specific applications. In addition to a description of the basic concept, we provide examples that illustrate the circumnavigation of obstacles, the steering of geometric complexity and the cable layout optimization in the presence of topographic variations.